PENGARUH PENERAPAN MODEL PEMBELAJARAN MATEMATIKA KNISLEY (MPMK) MENGGUNAKAN MEDIA PETAK WARNA-WARNI TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM PEMBELAJARAN SEGITIGA DI KELAS VII MTs. PUTRA-PUTRI SIMO - Elvira Rosa (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2017)
This research is motivated by the low ability of students' mathematical understanding and the use of model and instructional media given by teachers during this time is still less effective because the dominant learning model is centered on the teacher that is conventional learning. The purpose of this study is to determine whether or not there is a significant difference between students’ mathematical understanding abilities that follow Knisley's mathematical learning model (MPMK) using colorful plot media with students' mathematical understanding abilities that follow conventional learning. This research was conducted in MTs. Putra-Putri Simo from VII class on triangular material with sample of 30 students as experiment class and 30 student of control class. Data collection method used is a test method consisting of pretest and posttest ability of mathematical understanding. Data analysis in this research is by using distribution normality test, sample homogeneity test, and t-test. Based on the result of data analysis, it can be concluded that there is a significant difference between students 'mathematical understanding abilities that follow Knisley's mathematical learning model (MPMK) using colorful plot media and students' mathematical understanding abilities that follow conventional learning.